Products from the Reactions of 4-(4-Methoxybenzoyl)-5-(4-Methoxyphenyl)-2,3-Furandione with Aryl Isocyanates - Sacmaci, Mustafa; Akcamur, Yunus (Asian Journal of Chemistry, 2016)
4-(4-Methoxybenzoyl)-5-(4-methoxyphenyl)-2,3-furandione (1) reacted with aryl isocyanates to give novel pyrrolo[2,3-d] pyrimidines (deazapurines) 2 and 1,3-oxazine-2,4-diones 3 under different conditions. The reaction pathways leading to 2 and 3 include [4 + 2] cycloaddition processes and decarboxylation across the (C=N) bond of the aryl isocyanate accompanied by rearrangements. N1-(1-naphthyl)-2-[2,4-di(4-methoxyphenyl)benzo[h]quinolin-3-yl]-2-oxoacetamide (4) was obtained from the thermolysis of 2d. The formation of 4 proceeded via the iminobenzylfurandione as probable intermediate. The synthesis of new examples 1,3-oxazine-2,4-diones and pyrrolo[2,3d]pyrimidines following the unknown procedure and subsequent reactions using 1 and different aryl isocyanates has been reported.